FUZZY SUBJECTIVE EVALUATION OF ASIA PACIFIC AIRPORT SERVICES (Journal of Information and Communication Technology, 2010)
This paper presents a fuzzy decision-making model to determine the ranking of fourteen Asia Pacific airports based on the services provided to passengers. Airport services were represented by six attributes namely comfort, processing time, convenience, courtesy of staff, information visibility and security. Data for the attributes given by travel experts are in the triangular fuzzy number form. Based on fuzzy set and approximate reasoning, the model allows decision makers to make the best choice in accordance with human thinking and reasoning processes. The use of fuzzy rules which are extracted directly from the input data in making evaluation, contributes to a better decision and is less dependent on experts. Experimental results show that the proposed model is comparable to previous studies. The model is suitable for various fuzzy environments.